Is there an optimal speed for economical running? - Black, M. I.; Handsaker, J. C.; Allen, S. J.; Forrester, S. E.; Folland, J. P. (International Journal of Sports Physiology and Performance, 2018)
The influence of running speed and sex on running economy is unclear and may have been confounded by measurements of oxygen cost that do not account for known differences in substrate metabolism, across a limited range of speeds, and differences in performance standard. Therefore, this study assessed the energy cost of running over a wide range of speeds in high-level and recreational runners to investigate the effect of speed (in absolute and relative terms) and sex (men vs women of equivalent performance standard) on running economy. To determine the energy cost (kcal/kg·km) of submaximal running, speed at lactate turn point (sLTP), and maximal rate of oxygen uptake, 92 healthy runners (high-level men, n=14; high-level women, n=10; recreational men, n=35; recreational women, n=33) completed a discontinuous incremental treadmill test. There were no sex-specific differences in the energy cost of running for the recreational or high-level runners when compared at absolute or relative running speeds (P>.05). The absolute and relative speed-energy cost relationships for the high-level runners demonstrated a curvilinear U shape with a nadir reflecting the most economical speed at 13 km/h or 70% sLTP. The high-level runners were more economical than the recreational runners at all absolute and relative running speeds (P<.05). These findings demonstrate that there is an optimal speed for economical running, there is no sex-specific difference, and high-level endurance runners exhibit better running economy than recreational endurance runners.